Association between cardiometabolic index and erectile dysfunction: A new index for predicting cardiovascular disease. Issue 12 (4th November 2016) - Dursun, Murat; Besiroglu, Huseyin; Otunctemur, Alper; Ozbek, Emin
Abstract: Over the past decade, it has been suggested that erectile dysfunction (ED) is an early indicator of cardiovascular disease. In a recent study, a new index, termed as cardiometabolic index (CMI), was defined and measured as the product of triglyceride (TG)/high‐density lipoprotein‐cholesterol (HDL‐C) ratio and waist‐to‐height ratio, which are good predictors of coronary artery disease and main components of metabolic syndrome (MetS). All components of the CMI are also included in MetS criteria. Thus, we decided to evaluate the correlation between CMI, including the criteria of MetS, and ED. A total of 95 men with ED (ED group) and 82 healthy men (control group) were included in the study. Sexual functions were evaluated using the International Index of Erectile Function‐5 items scale. CMI was measured as the product of waist‐to‐height ratio and TG/HDL‐C ratio. Mean CMI level was 2.33 ± 0.11 in the study group and 1.14 ± 0.076 in the control group. CMI levels were significantly higher in the ED group ( p < 0.001). Because of the simplicity of measuring waist circumference, height measurement, and TG and HDL levels, CMI is an easily applicable index for evaluating cardiovascular dysfunction. ED is thought to be a precursor sign for vascular disease and a potential marker for atherosclerosis, endothelial dysfunction, and cardiovascular disease. In this context, CMI can be a useful index for the evaluation and calculation of ED risk, which was used for evaluation of cardiometabolic risk.